2008
DOI: 10.1016/j.jcrs.2008.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness measured by the Orbscan II system, contact ultrasound pachymetry, and the Artemis 2 system

Abstract: Purpose-To compare central corneal thickness measurements obtained by Orbscan II, contact ultrasound pachymetry and the non-contact Artemis-2 scanning ultrasound system. Methods-The central corneal thickness of 40 eyes (20 normal subjects) was measured using first the Orbscan II, followed by contact ultrasound pachymetry, and finally by the Artemis-2. Results were compared statistically using ANOVA, paired T-tests, and Bland-Altman plots.Results-One-way ANOVA showed a significant difference between the three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…We found Visante OCT CCT to average 8 μm thinner than Artemis 2 immersion high-frequency ultrasound. Paul et al 17 found Artemis 2 CCT values to average 11 μm thinner than USP, which, together with the 8-μm difference observed in our present study, suggests an expected difference between Visante and USP of ~19 μm. This is comparable to differences, averaging ~15 μm, reported in several studies comparing USP with Visante.…”
Section: Discussionsupporting
confidence: 79%
“…We found Visante OCT CCT to average 8 μm thinner than Artemis 2 immersion high-frequency ultrasound. Paul et al 17 found Artemis 2 CCT values to average 11 μm thinner than USP, which, together with the 8-μm difference observed in our present study, suggests an expected difference between Visante and USP of ~19 μm. This is comparable to differences, averaging ~15 μm, reported in several studies comparing USP with Visante.…”
Section: Discussionsupporting
confidence: 79%
“…There are several theoretical explanations for the discrepancy between both optical methods and UP in measuring the CCT. These include decentration, oblique incidence of the probe to the cornea, possible effect of topical anaesthesia with contact pachymetry and the variability of ultrasound speed in tissues of different hydration (Gonzalez-Meijome et al 2003;Nemeth et al 2006;Paul et al 2008). The accuracy of UP is operator dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study3 comparing Artemis-2 CCT measurements with those of a hand-held ultrasound pachymeter, the Artemis-2 measured significant thinner (11 μm) CCT values when compared with ultrasound pachymetry in normal subjects. This could be due to the fact that our sample was more homogeneous considering the ages of the subjects and, as such, less prone to variations.…”
Section: Discussionmentioning
confidence: 92%
“…Accurate measurement of CCT with the hand-held ultrasound pachymeter relies on placement of the probe as close as possible to the central cornea. Higher values will be obtained if the probe is not placed at 90 degrees to the corneal surface or if placed slightly off center 3. With hand-held ultrasound pachymetry, the same place on the cornea is not measured on every occasion, and because the cornea varies in thickness according to location, this adds to some error.…”
Section: Introductionmentioning
confidence: 99%